Volume 1: Offshore Technology 2009
DOI: 10.1115/omae2009-80212
|View full text |Cite
|
Sign up to set email alerts
|

Linearization of Quadratic Drag to Estimate CALM Buoy Pitch Motion in Frequency-Domain and Experimental Validation

Abstract: Estimate of the pitch motion of an oil offloading Catenary Anchor Leg Mooring (CALM) buoy is presented. Linearization of the quadratic drag/damping term is investigated by the frequency-domain analysis. The radiation problem is solved to estimate the added mass and radiation damping coefficients, and the diffraction problem is solved for the linear wave exciting loading. The equation of motion is solved by considering the linearized nonlinear drag/damping. The pitch motion response is evaluated at each wave fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is noteworthy that this validation approach is conducted here using experimental modelling. It is also based on application by considering some models studied on existing theoretical marine hose models [96][97][98][99][100] and experimental hose models [147][148][149][150]. These models were compared to that of this present study and showed effective similarities in hose behaviour.…”
Section: Touch Down Point(tdp)mentioning
confidence: 99%
“…It is noteworthy that this validation approach is conducted here using experimental modelling. It is also based on application by considering some models studied on existing theoretical marine hose models [96][97][98][99][100] and experimental hose models [147][148][149][150]. These models were compared to that of this present study and showed effective similarities in hose behaviour.…”
Section: Touch Down Point(tdp)mentioning
confidence: 99%
“…However, it is crucial to investigate the effect of nonlinear seabed models on CALM buoy systems and on submarine hoses, as this has not been studied. Although it has been shown that hoses are affected by the motions of the main CALM buoy [59][60][61][62][63], the effect of the buoy motion on the hose behaviour has not been quantitatively studied. This gap includes hose behaviour relative to the effective tensions, fatigue, full loading history, curvature, and minimum bending radius (MBR) on nonlinear seabeds.…”
Section: Introductionmentioning
confidence: 99%